Isolation and identification of the causative agent of fowl cholera in ‎Iraq and preparation of vaccines against the disease ‎2- Preparation of different vaccines against fowl cholera disease - M .Mhanam‎, Hatem; K. Kassab‎, Ather; K. Shubber‎, Esmail (The Iraqi Journal of Veterinary Medicine, 2005)
Three types of locally isolated Pasteurella multocida antigenes namely the whole sonicated bacteria (WSB) the bacterial cell wall (BCW) and the lipopolysaccharide (LPS) of bacteria were prepared as a vaccine . Each type of antigenes was used in 3 concentrations that are 107, 109 and 1011 Colony Forming Units / bird for WSB and 250,500 and 750 mg/bird for BCW and LPS. Each of the prepared concentrations was injected subcutaneously into a group of broiler breeder chickens and one group was left as a control . The groups were vaccinated 2 times at 10 and 18 weeks. The progress of immune response was monitered throughout a passive haemagglutination, an agar gel immunodiffusion, delayed type hypersensitivity and challenge tests. The results demonstrated that the WSB antigens provided better protection and the concentration of 109 was the superior of all. The BCW antigen was next and the concentration of 500 mg/bird was the best among these antigenes, followed by LPS antigen and the best concentration among them was the 750 mg/bird.